Climate Change Litigation in Private Nuisance: Can It Address Harms Sustained by Traditional Owners in the Torres Strait? - Nia Emmanouil; Martina Popa; Anne Kallies (2021)
Torres Strait Islanders are highly vulnerable to climate change hazards and in turn, climate-related harms. Through a detailed analysis of Australian and foreign case law and commentary, this article examines whether tort law, specifically, private nuisance, may offer Traditional Owners in the Torres Strait an avenue for holding accountable major carbon polluters for their contribution to these climate-related harms. Barriers to success are analysed and further discussed in relation to policy questions. Ultimately, the article finds that significant barriers to success currently exist, making a climate-related harm claim in private nuisance unlikely to succeed, for now. However, advances in international and Australian jurisprudence are creating the potential for actions to be successful in the future.